EXCHANGE RATE VOLATILITY, FOREIGN DIRECT INVESTMENT, AND ECONOMIC GROWTH IN NIGERIA: EVIDENCE FROM COINTEGRATION AND ERROR CORRECTION ANALYSIS - AGBANA, JOHN; Esther, OLOWOLA Omobolanle Oladoyin (ShodhKosh: Journal of Visual and Performing Arts, 2026)
This study examines the effects of exchange rate fluctuations and foreign direct investment on economic growth in Nigeria using annual time-series data from 2000 to 2024. The study applies Augmented Dickey-Fuller unit root tests, Engle-Granger cointegration tests, and an Error Correction Model to evaluate both long-run equilibrium relationships and short-run dynamics among the variables. The results show that exchange rate depreciation exerts a negative but statistically insignificant effect on foreign direct investment inflows. In contrast, foreign direct investment has a positive and statistically significant effect on economic growth. The unit root results indicate that the variables are non-stationary at levels but become stationary after first differencing. At the same time, the cointegration test confirms the existence of a long-run relationship among the exchange rate, foreign direct investment, and economic growth. The error correction results reveal a negative and significant adjustment coefficient, indicating that short-run deviations from equilibrium are corrected over time. The findings suggest that economic growth in Nigeria responds more to structural and institutional factors than to short-run movements in the exchange rate and capital inflows. The study concludes that sustained macroeconomic stability, improved governance, and sectoral diversification are critical for enhancing the growth impact of foreign direct investment. The study recommends that monetary authorities strengthen exchange rate stability through transparent and market-supportive policies to reduce uncertainty and improve investor confidence. It also recommends that policy efforts focus on attracting foreign direct investment to productive sectors such as manufacturing, agriculture, technology, and renewable energy to promote employment, productivity, and long-term economic growth.